Membantu Remaja Tunarungu Meraih Masa Depan: Peran Program Keterampilan Dalam Pemilihan Karir Bagi Remaja Tuna Rungu SLBN Kotagajah - Selviani, Mega; Ika Ariati; Andika Ari Saputra (Scidac Plus, 2024)
Hearing loss can create obstacles in communication and social interaction, resulting in difficulties in education, career and daily life. This makes deaf teenagers need to have special skills to overcome these obstacles and achieve success.. The aim of this research is to analyze the skills program at the Kotagajah State Special School and how the program helps deaf students in determining careers. This research method uses descriptive qualitative. Data was taken through observation, interviews and documentation and validated using data analysis techniques. Next, the data was analyzed by means of data reduction, data presentation, and conclusions. The research results show that Kotagajah State SLB equips its students with 8 soft skills programs for their future.This program assists deaf students in determining careers, helps them identify their interests and talents, develops the skills needed to achieve the desired career. In conclusion,The skills program at the Kotagajah State Special School is one of the effective guidance and counseling strategies in helping deaf teenagers determine their careers. Keywords: Deaf teenagers, career determination, skills program